Image and Logic: A Material Culture of Microphysics by Peter Galison - Julia Gelfand (Issues in Science and Technology Librarianship, 1997)
This article reviews the book Image and Logic:  A Material Culture of Microphysics. Chicago: University of Chicago Press, 1997, by Peter Galison.